What Determines Banks' Market Power? Akerlof versus Herfindahl - Moshe Kim; Eirik Gaard Kristiansen; Bent Vale (Norges Bank, 2005)
We introduce a model analyzing how asymmetric information problems in a bank-loan market may evolve over the age of a borrowing firm. The model predicts a life-cycle pattern for banks' interest rate markup. Young firms pay a low or negative markup, thereafter the markup increases until it falls for old firms. Furthermore, the pattern of the life-cycle depends on the informational advantage of the inside bank and when more dispersed borrower information yields fiercer bank competition. By applying a new measure of the informational advantage of inside banks and a large sample of small Norwegian firms, we find empirical support for the predicted markup pattern. We disentangle effects of asymmetric information (Akerlof effect) from effects of a concentrated banking market (Herfindahl effect). Our results indicate that the interest rate markups are not influenced by bank market concentration.
hdl:11250/2498431
Keywords: G21; L15; 330; banking; risk-pricing; lock-in